Job Satisfaction and Organizational Commitment as Predictors of Organizational Citizenship and In-Role Behaviors - Williams, Larry J.; Anderson, Stella E. (Journal of Management, 1991)
Previous organizational citizenship behavior (OCB) research (a) has not demonstrated that extra-role behaviors can be distinguished empirically from in-role activities, and (b) has not examined the relative contributions of components ofjob satisfaction a nd organizational commitment to the performance of OCBs. Factor analysis of survey data from 127 employees' supervisors supported the distinction between in-role behaviors and two forms of OCBs. Hierarchical regression analysis found two job cognitions variables (intrinsic and extrinsic) to be differentially related to the two types OCBs, but affective variables and organizational commitment were not significant predictors. The link between the present findings and previous research is discussed, as are directions forfuture research.